2012
DOI: 10.1186/1743-422x-9-212
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with live virus vaccine protects highly susceptible DBA/2J mice from lethal influenza A H1N1 infection

Abstract: BackgroundThe mouse represents an important model system to study the host response to influenza A infections and to evaluate new prevention or treatment strategies. We and others reported that the susceptibility to influenza A virus infections strongly varies among different inbred mouse strains. In particular, DBA/2J mice are highly susceptible to several influenza A subtypes, including human isolates and exhibit severe symptoms after infection with clinical isolates.FindingsUpon intra-muscular immunization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The robust response of DBA.2 mice with an approximately 1000-fold acute increase in SAA levels at 3 dpi implies that DBA.2 mice are much more susceptible to influenza virus infections than C57BL/2 or Swiss-Webster mice. This observation has also been made by others (Dengler et al, 2012; Pica et al, 2011). DBA.2 mice offer the additional advantage of being susceptible to influenza viruses that have not been mouse-adapted (Boon et al, 2010; Kim et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The robust response of DBA.2 mice with an approximately 1000-fold acute increase in SAA levels at 3 dpi implies that DBA.2 mice are much more susceptible to influenza virus infections than C57BL/2 or Swiss-Webster mice. This observation has also been made by others (Dengler et al, 2012; Pica et al, 2011). DBA.2 mice offer the additional advantage of being susceptible to influenza viruses that have not been mouse-adapted (Boon et al, 2010; Kim et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…1C and 1D), similar to BALB/c mice. This result suggests that the high susceptibility of DBA/2 mice to influenza viruses may not be due to impaired immune responses against influenza viruses (Dengler et al, 2012) and that the DBA/2 mouse model may be otherwise comparable with other mouse models.…”
Section: Pathogenicity Of the Ph1n1 K/09 Virus In Balb/c Versus Dba/2...mentioning
confidence: 73%
“…However, evaluation of antiviral drug efficacy with a mouse-adapted virus in vivo can be complicated by genetic changes in the virus genome during the mouse adaptation process (Sakabe et al, 2011;Zhu et al, 2012). Thus, DBA/2 mice, which do not require prior adaptation of most influenza viruses, have been actively utilized in studies on the functions of influenza viral proteins (Hai et al, 2010), potentials of antibody therapy (Boon et al, 2010;Kashyap et al, 2010), and vaccine efficacy (Solorzano et al, 2010;Dengler et al, 2012). Using an un- adapted virus is critically important for testing the efficacy of anti-influenza drugs against human-infecting viruses, particularly during the drug development stage, as the antiviral effect of the drug should not be against the mouseadapted virus but ultimately against the original humaninfecting virus.…”
Section: Introductionmentioning
confidence: 99%
“…However, as we chose to use a wild-type human isolate without mouse adaptation in these studies, the DBA/2J model was used, based on the results of the comparison studies. The DBA/2J model has been used extensively in influenza virus studies and has been shown to be a suitable, well characterized model to evaluate influenza vaccines [ 26 30 ], although the mechanism of susceptibility to H7N9 infection may not be as well understood as in the BALB/c mouse model.…”
Section: Discussionmentioning
confidence: 99%